基于数据直接传递的摆线轮参数化设计 - 林昌华; 杨岩 (Jixie chuandong)
Based on direct data transfer,a new modeling method in UG is presented.The fast modeling of cycloid-gear whose 2D profile data generated in AutoLISP is achieved by this method.Using the file function of spline curve in UG modeling module,the data calculated by AutoLISP is loaded in UG.The 2D profile of cycloid-gear is directly obtained,and then,the 3D model is constructed by extruded body and other functions.The problem of data transferred in different software is successfully solved by this method.